The Neuroanatomical Correlates of Dyspnea: An Activation Likelihood Estimation Meta-Analysis - Christoph Müller; Jens Kerl; Dominic Dellweg (NeuroSci)
The sensation of dyspnea is related to various cardiopulmonary and neuromuscular diseases and is characterized by its sensory and affective qualities. Although there is a vast number of studies investigating its pathophysiology, less is known about the neuroanatomy of dyspnea perception. An activation likelihood estimation (ALE) meta-analysis of 13 studies investigating different breathing challenges using either PET or fMRI was performed to demonstrate the neuroanatomical correlates of dyspnea perception. The ALE meta-analysis was performed using the GingerAle software 3.0.2 and was displayed with the Mango software 4.1. Synthesizing the results of all included studies, clusters involving the insula and cingulated cortex in both hemispheres were observed. Subgroup analysis for the restrained breathing condition revealed activation involving the right and left cingulate cortex and left anterior cingulate cortex. For the loaded breathing condition, statistically significant activation was found for the postcentral gyrus, the superior temporal gyrus, and the right thalamus. The combined ALE map for both conditions showed activity patterns in the right cingulate cortex, the right insula, and the right thalamus. This ALE meta-analysis demonstrates that two separate neuronal pathways related to either the affective or intensity domain are involved in the central processing of dyspnea perception.